2009
DOI: 10.3767/003158509x471052
|View full text |Cite
|
Sign up to set email alerts
|

<I>Calonectria</I> (<I>Cylindrocladium</I>) species associated with dying <I>Pinus</I> cuttings

Abstract: Calonectria (Ca.) species and their Cylindrocladium (Cy.) anamorphs are well-known pathogens of forest nursery plants in subtropical and tropical areas of the world. An investigation of the mortality of rooted Pinus cuttings in a commercial forest nursery in Colombia led to the isolation of two Cylindrocladium anamorphs of Calonectria species. The aim of this study was to identify these species using DNA sequence data and morphological comparisons. Two species were identified, namely one undescribed species, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 32 publications
3
61
0
Order By: Relevance
“…(2015) Ca. brassicae CBS 111869 T AF232857GQ267382FJ918567DQ190720KM232308GQ280576GQ280698Crous et al., 1999, Crous et al., 2006a, Crous et al., 2006b, Lombard et al., 2009, Lombard et al., 2010c, present study Ca. brassicicola CBS 112841 T KX784619KX784561KX784689Lombard et al.…”
Section: Resultsmentioning
confidence: 99%
“…(2015) Ca. brassicae CBS 111869 T AF232857GQ267382FJ918567DQ190720KM232308GQ280576GQ280698Crous et al., 1999, Crous et al., 2006a, Crous et al., 2006b, Lombard et al., 2009, Lombard et al., 2010c, present study Ca. brassicicola CBS 112841 T KX784619KX784561KX784689Lombard et al.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of homothallic and heterothallic mating strategies in closely related fungi is interesting and could well provide another opportunity to analyse the genetics of mating systems in ascomycetes. This study has shown, however, that morphology in combination with phylogenetic inference provides the most useful approach to identify cryptic species in Calonectria (Lombard et al 2009). The present study has also shown the importance of the multi-gene approach in studying the phylogenetic relationships of phenotypic closely related Calonectria spp.…”
Section: Discussionmentioning
confidence: 98%
“…Calonectria pseudoecuadoriae and C. plurilateralis (Ecuador) are both new additions to the C. brassicae and C. cylindrospora species complexes, respectively (Crous, 2002, Lombard et al., 2009, Alfenas et al., 2015). Calonectria pseudoecuadoriae is morphologically similar to C. ecuadoriae (Crous et al.…”
Section: Discussionmentioning
confidence: 99%
“…In other regions, such as southern Africa and Australia, Calonectria spp. appear mostly to be limited to forestry nurseries (Crous, 2002, Lombard et al., 2009, Lombard et al., 2010a, Lombard et al., 2010b, Lombard et al., 2010c). In agricultural and horticultural crops, Calonectria spp.…”
Section: Introductionmentioning
confidence: 99%